Performance of maturity transformation strategies - Christoph Schmidhammer; Vanessa Hille; Arnd Wiedemann (Deutsche Bundesbank, 2020)
This paper analyses theperformance ofmaturity transformation strategiesduring a period of high and low interest rates. Based on German government bond yieldsfrom September 1972 to May 2019,we construct a rolling window of bond ladders where long-term assets are financed by short-term liabilities. Risk and return increase significantly with maturity gaps for both sample periods. During theperiod of low interest rates,dominant strategies can be observed for short-term and medium-term gaps.With respect to different financial reporting standards,weaddress maturity transformation results froman earnings-based perspective as well as froma market value-based perspective.
Keywords: G11; G12; G21; 330; Maturity Transformation; Bond Ladders; Period of Low Interest Rates; Performance; Interest Rate Risk